2018
DOI: 10.1371/journal.pntd.0006251
|View full text |Cite
|
Sign up to set email alerts
|

Clonorchis sinensis adult-derived proteins elicit Th2 immune responses by regulating dendritic cells via mannose receptor

Abstract: BackgroundClonorchis sinensis (C. sinensis) is the most widespread human liver fluke in East Asia including China and Korea. Clonorchiasis as a neglected tropical zoonosis, leads to serious economic and public health burden in China. There are considerable evidences for an etiological relation between chronic clonorchiasis and liver fibrosis in human beings. Liver fibrosis is a highly conserved and over-protected response to hepatic tissue injury. Immune cells including CD4+ T cell as well as dendritic cell (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 47 publications
(61 reference statements)
1
20
0
Order By: Relevance
“…sinensis has evolved complex mechanisms for resistance to immune responses. Zhao et al demonstrated that total protein from C. sinensis inhibited Th1 immune responses by the activation of mannose receptor (MR), but not TLR2 or TLR4 to induce Th2-skewed response [15]. Our previous study showed that during the secretion of ESPs by C. sinensis, TLR4 plays a regulatory role in the induction of type I-relative cytokines (such as IFN-γ, IL-12, IL-6, TNFα) [14].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…sinensis has evolved complex mechanisms for resistance to immune responses. Zhao et al demonstrated that total protein from C. sinensis inhibited Th1 immune responses by the activation of mannose receptor (MR), but not TLR2 or TLR4 to induce Th2-skewed response [15]. Our previous study showed that during the secretion of ESPs by C. sinensis, TLR4 plays a regulatory role in the induction of type I-relative cytokines (such as IFN-γ, IL-12, IL-6, TNFα) [14].…”
Section: Discussionmentioning
confidence: 99%
“…Zhao et al demonstrated that total protein from C . sinensis inhibited Th1 immune responses by the activation of mannose receptor (MR), but not TLR2 or TLR4 to induce Th2-skewed response [ 15 ]. Our previous study showed that during the secretion of ESPs by C .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations